COMMUNICATION BETWEEN NURSES AND LABORATORY STAFF AND ITS EFFECT ON TURNAROUND TIME OF TEST RESULTS. - Mowidi Ratyan Mater Alhazmi, Amirah Ayed F. Alanazi, Manal Ayad Mukhlef Alenzi, Hanan Rabai Alharbi, Bdour Mthgal Khawailed Alruwaili, Maram Khalil Ayed Alanazi (JOURNAL OF PHARMACEUTICAL ANALYSIS, 2025)
Effective communication between nurses and laboratory staff is essential for ensuring timely diagnostic processes and supporting safe clinical decision-making. Turnaround time (TAT) of laboratory test results is a critical quality indicator that directly influences patient flow, treatment initiation, and overall healthcare outcomes. Communication gaps, unclear test requests, specimen handling errors, and delays in reporting can significantly prolong TAT and compromise patient safety. This paper explores the impact of nurse–laboratory communication on laboratory test turnaround time, highlighting the role of standardized communication, clear documentation, timely specimen transport, and interprofessional collaboration. Strengthening communication pathways and promoting teamwork between nursing and laboratory services can reduce delays, enhance workflow efficiency, and improve the quality of patient care.